Firm Size as a Moderator in Food and Beverage Companies on the IDX: Tax Planning and Earnings Persistence - Khusnul Khotimah; Anissa Yuniar Larasati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to examine how tax planning affects earnings persistence in food and beverage manufacturing companies listed on the Indonesia Stock Exchange, using firm size as a moderating variable. Stock Exchange from 2021 to 2024. Using secondary data from annual financial reports, the study employs a quantitative methodology. Purposive sampling was used to determine the sample, which produced 164 observations from 41 manufacturing companies in the food and beverage subsector between 2021 and 2024. With the aid of SPSS vs. 27 software, moderated regression analysis was used to analyze the data. The test results demonstrate that tax planning has a positive and significant impact on earnings persistence to some extent, suggesting that better tax planning is typically followed by higher earnings persistence. However, the relationship between tax planning and earnings persistence is not significantly affected by firm size, nor does it function as a moderating variable. As a result, the impact of tax planning on earnings persistence is essentially the same for both small and large businesses.